Roles, Functions and Challenges of Hospital Management Committees in Busia County, Kenya - William N. Okedi; Ferdinard Adungo (Emerging Trends in Disease and Health Research Vol. 9, 2022)
In 2009, Kenya’s Ministry of Health reformed the health sector with the purpose of promoting and improving citizens’ health. It founded the Hospital Management Services Fund, which will be managed at the facility level by the Hospital Management Committees (HMCs). Since the HMCs were established at the county level following the devolution of health care in 2016, no review of their performance has been conducted in Busia County. The main goals of devolution include among others to promote social and economic development as well as the provision of proximate, easily accessible services throughout Kenya. We evaluated the HMCs’ selection criteria, orientation, induction, and performance in Busia, as well as their implications for Kenya and other African contexts. Through Focus Group Discussions and key informant interviews, data was obtained from all HMC members in six level 4 and one level 5 hospitals. Documents collected both at the facility and county levels were analysed and used appropriately. The National Guidelines were not fully followed by all seven hospitals examined. Three hospitals (43%) nominated individuals with educational levels below the needed O level certification. Another 33% (43%) violated Kenya’s 2010 Constitution by discriminating against people with disabilities and minorities. The study reveals widespread commissions and omissions in the recruitment process, which caused anxiety and frustration among HMC members, staff, and the hospitals’ catchment populations. Finally, because the nominated HMC members have not been gazetted, appointed, orientated, and facilitated, they lack the legal authority to assume their tasks and obligations.